Impact of Inadequate Experience and Skill on the Construction Sector in KwaZulu-Natal, South Africa - Ntuli, B.; Allopi, D. (Engineering, Technology & Applied Science Research, 2014)
Civil engineering contractors encounter serious challenges in order to sustain their businesses, especially in a weak economic climate. A certain level of construction experience, expertise and training are required to manage a sustainable construction company. The Construction Industry Development Board (CIDB) was established in 2000 as a statutory body to provide leadership to stakeholders and stimulate sustainable growth, reform and improvement of the construction sector for effective infrastructure delivery and improvement of construction skills. The objectives of this research were to investigate challenges faced by civil engineering contractors whilst making their enterprises sustainable. Contractors’ views were presented at “Construction Indaba 2011” held on 1–2 June 2011 and hosted by eThekwini Municipality’s Business Support, Tourism and Markets in Durban KwaZulu-Natal. Discussion and findings revealed to a skills’ shortage in the construction section and underlined the need for continuous training of the contractors’ employees. The South African government in conjunction with all stakeholders should develop and implement contractor programs to address the lack of technical and management skills in the construction sector.